Characteristics of solar radiation in a Pinus radiata stand (Valdivia, Chile) - Huber, A. W.; Oyarzún, C. E.; Álvarez, L. A.; Araya, E. (Bosque (Valdivia), 1988)
Spatial and temporal distribution of the direct solar beam and diffuse radiation were studied in an adult Pinus radiata stand. Solarimeters (direct solar beam) and shaded pyranometers (diffuse radiation) located above the forest (43 m), at the mean height of initial canopy (20 m) and close to the ground (2 m) provided the data for the study. The diffuse radiation shows the highest penetration down to the forest ground, with averages, of 30.2% and 10.4% on clear and cloudy days, respectively, where as the direct solar beam amounted to 4.4.% and 2.5% for the same days. The direct solar component within the canopy increases during summer, as opposed to the diffuse component which is less variable along the year. Temporal fluctuations of solar radiation within the forest are related to an unequal penetration of the direct solar beam.